Формування іміджу підпиємства як фактору його конкурентоспроможності - Мірошник, Марія Володимирівна; Чернобровкіна, Світлана Віталіївна; Журавльова, М. О. (НТУ "ХПІ", 2014)
В статті проаналізовано загальні тенденції формування іміджу підприємства , визначено, що імідж підприємства є сукупністю бажаного, реального та необхідного іміджу. Розроблена Канва цінності продукту / послуги, яка допомагає проектувати, тестувати і формувати пропоновану споживачам цінність більш структурованим і продуманим методами. За результатами досліджень побудована "зірка" відповідності окремих показників іміджу ціннісній орієнтації споживачів.

The article analyzes the general trends of image formation of the company, it is determined that Midge enterprise – as bipolar phenomenon is based on multifactorial assessment and is a collection of such components as desired, the real and the desired image. It was established that theformation of positive image becomes crucial value aspect, the implementation of which allows the company to explore the intrinsic motivation of consumers to reflect their value orientations and purchasing behavior. Designed Canvas value product / service that helps you design, test and build the value offered to consumers in a more structured and deliberate manner. According to studies (fragmentary) constructed "star" image of conformity of individual indicators known supermarket value orientation of consumers.
Formation of the company's image as a factor of competitiveness
Keywords: трансринкові відносини; корпоративний імідж; цінності споживача; інноваційні підходи; image; enterprise; consumer; consumer values